2017
DOI: 10.1111/andr.12347
|View full text |Cite
|
Sign up to set email alerts
|

Testosterone level and endothelial dysfunction in patients with vasculogenic erectile dysfunction

Abstract: The association between endothelial dysfunction and late onset hypogonadism (LOH) in patients with vasculogenic erectile dysfunction (ED) is not yet well settled. Our objective was to assess the association between LOH and endothelial dysfunction in patients with vasculogenic ED. Throughout 2014-2015 a total of 90 men were enrolled in this cross-sectional observational study. Of them 60 patients with a clinical diagnosis of ED were further subdivided into two equal groups: patients with vasculogenic ED and LOH… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 39 publications
0
10
0
Order By: Relevance
“…Based on the published data of the different clinical characteristics of the post-stroke patients with ED and the non-ED stroke patients, in the risk stratification of patients before the stroke event, individuals with psychosocial disorders (i.e., depression and anxiety), medication use (i.e., antihypertensive drug), comorbidities (i.e., diabetes, hypertension, and hypercholesterolemia), and co-existing medical conditions (i.e., older age, smoking, and obesity) were more vulnerable to suffer from ED than those without these risk factors. In addition to these clinical characteristics, the endothelial dysfunction markers, endothelial progenitor cells (EPCs), and endothelial microparticles are considered to serve as the serum biomarkers for both ED ( 62 ) and stroke events ( 63 ). Since there is a close association between stroke and ED, either from stroke to ED or from ED to stroke, the low level of EPCs and endothelial microparticles may help to predict those patients with ED at high risk of stroke as well as those stroke patients at high risk of ED.…”
Section: Discussionmentioning
confidence: 99%
“…Based on the published data of the different clinical characteristics of the post-stroke patients with ED and the non-ED stroke patients, in the risk stratification of patients before the stroke event, individuals with psychosocial disorders (i.e., depression and anxiety), medication use (i.e., antihypertensive drug), comorbidities (i.e., diabetes, hypertension, and hypercholesterolemia), and co-existing medical conditions (i.e., older age, smoking, and obesity) were more vulnerable to suffer from ED than those without these risk factors. In addition to these clinical characteristics, the endothelial dysfunction markers, endothelial progenitor cells (EPCs), and endothelial microparticles are considered to serve as the serum biomarkers for both ED ( 62 ) and stroke events ( 63 ). Since there is a close association between stroke and ED, either from stroke to ED or from ED to stroke, the low level of EPCs and endothelial microparticles may help to predict those patients with ED at high risk of stroke as well as those stroke patients at high risk of ED.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, T replacement therapy in hypogonadal men improved erectile function by modulating endothelial progenitor cells 33 . Omar et al indicated a significant increase in endothelial progenitor cells and endothelial microparticles levels in patients with both vasculogenic ED and late‐onset hypogonadism 34 . Increased NO bioavailability in erectile tissue, because of varying T levels, may lead to both parasympathetic hyperactivity and upregulation of NO signaling in HCC.…”
Section: Discussionmentioning
confidence: 99%
“…EPCs could have different possible phenotypes and are implicated in the vasculogenic reparative process and the consequent re-endothelization after vascular injuries (54). Some EPC populations are decreased in hypogonadal patients (55), while other EPCs subtypes are present in higher concentration in patients with hypogonadism and ED, compared to eugonadal patients with ED (56). This last subpopulation of EPCs (i.e., EPCs CD45neg/CD34pos/CD144pos) could be considered a marker of vascular damage, in response to which they are produced in greater quantities in the attempt to repair the injured endothelium.…”
Section: Late-onset Hypogonadism and Erectile Dysfunctionmentioning
confidence: 99%